Phosphorylation of Ser-42 and Ser-59 in the N-terminal region of the tyrosine kinase p56lck. - Winkler, D G (1993)
Ser-42 and Ser-59 in the N-terminal region have been identified as the major phorbol ester-induced phosphorylation sites of p56lck. Phosphorylation of Ser-59 results in a gel shift from 56 kDa to 61 kDa. Simultaneous phosphorylation of Ser-42 and Ser-59 results in a further gel shift to 63 kDa. In vitro kinase assays show that Ser-59 can be uniquely phosphorylated by mitogen-activated protein kinase and that Ser-42 can be phosphorylated by either protein kinase A or protein kinase C.